(untitled) (ZAMONAVIY TARAQQIYOT VA FAN: 21-ASR YONDASHUVLARI, 2026)
This article presents considerations and rationale for the development of cognitive processes in adolescents during English language learning. The article reflects on the importance of cognitive development and examines the scientific and psychological aspects of cognitive development. At the same time, the development of cognitive processes is considered an important factor not only in intensifying the process of teaching a foreign language, but also in the professional growth of youths.